2021
DOI: 10.3389/fpsyg.2021.614451
|View full text |Cite
|
Sign up to set email alerts
|

A Translational Perspective of Maternal Immune Activation by SARS-CoV-2 on the Potential Prenatal Origin of Neurodevelopmental Disorders: The Role of the Cholinergic Anti-inflammatory Pathway

Abstract: The emergent Coronavirus Disease 2019 (COVID-19) caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) could produce a maternal immune activation (MIA) via the inflammatory response during gestation that may impair fetal neurodevelopment and lead to postnatal and adulthood mental illness and behavioral dysfunctions. However, so far, limited evidence exists regarding long-term physiological, immunological, and neurodevelopmental modifications produced by the SARS-CoV-2 in the human maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Recent but few experimental studies have shown the possible interest of HRV as physiological measurement parameter for COVID-19 patients 23,24 . However, this non-invasive approach to evaluate the activity of the ANS remains too little understood and requires further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent but few experimental studies have shown the possible interest of HRV as physiological measurement parameter for COVID-19 patients 23,24 . However, this non-invasive approach to evaluate the activity of the ANS remains too little understood and requires further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to infections during pregnancy is quite common; almost 50% of pregnant women get respiratory tract infections while close to 20% getting urinary tract infections; nonetheless this high prevalence of maternal infection results in neurodevelopmental abnormalities in only a small portion of the exposed offspring ( Milada et al, 2017 ; Weber-Stadlbauer, 2017 ; Brown and Meyer, 2018 ). This dichotomy might hold the key to certain protective that make certain pregnancies less susceptible to others, and mechanistically evidence has suggested impairment of cholinergic anti-inflammatory pathways in some pregnant mothers to be linked to a heightened inflammatory response ( Reyes-Lagos et al, 2021 ).…”
Section: Heterogeneity In Maternal Immune Activationmentioning
confidence: 99%
“…Based on its clinical manifestation and past “similar” infections, theories have been proposed that suggest potential effects on the offspring ( Granja et al, 2021 ). Following infection with SARS-CoV-2, there is an uncontrolled release of inflammatory cytokines and chemokines that have been involved in brain development [e.g., interleukins (IL-1β,−2,−4,−6,−8,−10), tumor necrosis factor alpha, interferons (IFN-α, IFN-γ)] ( Reyes-Lagos et al, 2021 ). Amid the exacerbated long-term inflammatory effects observed in COVID-19 patients and the lessons learned from of viral-mediated MIA effects on the progeny’s brain, it is crucial to consider the neurological consequences of maternal SARS-CoV-2 infection on the offspring.…”
Section: Potential Effects Of Sars-cov-2 On Fetal Brain Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although gestational timing has been shown to have differential effects in adolescent and adult offspring (11,22), it is unclear how it affects neurodevelopment in its early phase. A better understanding of the neurodevelopmental sequelae of MIA-exposure on very early brain development is of importance in the context of the current COVID-19 pandemic, as mothers who contracted the virus during pregnancy were more likely to have obstetric complications leading to poor fetal health outcomes such as low birth weight, intrauterine growth restriction, and preterm birth (23,24).…”
Section: Introductionmentioning
confidence: 99%